Long non-coding RNA CASC2 ameliorates sepsis-induced acute kidney injury by regulating the miR-155 and NF-κB pathway - Wang, Min; Wei, Jilou; Shang, Futai; Zang, Kui; Ji, Ting (International journal of molecular medicine, 2020)
Sepsis is a systemic inflammatory response syndrome that can cause multiple-organ damage, including acute kidney injury (AKI). Studies have shown that the long non-coding RNA cancer susceptibility candidate 2 (CASC2) is involved in the occurrence and development of multiple human diseases, although its expression and role in AKI has not yet been reported. The present study demonstrated that the expression of CASC2 was significantly decreased in the serum of patients with sepsis compared with healthy subjects. In addition, the CASC2 level was negatively associated with the severity of AKI. Further experiments revealed that CASC2 promoted cell viability and inhibited inflammatory factor secretion, apoptosis and oxidative stress in lipopolysaccharide-stimulated human renal tubular epithelial HK-2 cells. Importantly, the current study observed that CASC2 was negatively associated with a pro-inflammatory microRNA (miR)-155. In addition, the upregulation of CASC2 significantly suppressed the nuclear factor κB (NF-κB) signaling pathway. In conclusion, the results of the present study suggested that CASC2 may serve as a potential target for treating sepsis-induced AKI by inhibiting the miR-155 and NF-κB pathway-mediated inflammation.